2001
DOI: 10.1128/jcm.39.5.1771-1773.2001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Genotyping Based on 5′ Noncoding Sequence Analysis (Trugene)

Abstract: Hepatitis C virus (HCV) genotyping of samples from 184 patients with chronic HCV infection by the Trugene 5NC genotyping kit, based on sequence analysis of the 5 noncoding region (5 NCR), and the InnoLiPA assay was evaluated. In addition to these methods, the 184 samples were also analyzed by sequencing of part of the NS5B of the HCV genome after in-house PCR amplification, as a means of validating results obtained with the 5 NCR. The distribution of the genotypes typed by NS5B sequence analysis was as follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 31 publications
8
48
0
2
Order By: Relevance
“…Also, in accordance with previous studies 6,8,12,14,17,18,21 , discrepant results at the subtype level, mainly subtypes 1a and 1b, were found here (two samples identified as 1a by NS5B sequencing were subtyped as 1b by 5' NC sequencing). Although both regions provide similar results at the genotype level, which is adequate for clinical practice, especially in the management of antiviral therapy, the NS5B sequencing appears to be more useful for epidemiological investigations.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Also, in accordance with previous studies 6,8,12,14,17,18,21 , discrepant results at the subtype level, mainly subtypes 1a and 1b, were found here (two samples identified as 1a by NS5B sequencing were subtyped as 1b by 5' NC sequencing). Although both regions provide similar results at the genotype level, which is adequate for clinical practice, especially in the management of antiviral therapy, the NS5B sequencing appears to be more useful for epidemiological investigations.…”
Section: Resultssupporting
confidence: 71%
“…As observed by other authors 6,8,12,18 , no difference at the genotype level was found for the 42 samples that could be successfully amplified and sequenced in the the 5' NC and NS5B regions. Also, in accordance with previous studies 6,8,12,14,17,18,21 , discrepant results at the subtype level, mainly subtypes 1a and 1b, were found here (two samples identified as 1a by NS5B sequencing were subtyped as 1b by 5' NC sequencing).…”
Section: Resultssupporting
confidence: 62%
“…Sequencing the HCV 5'UTR has proved effective in discriminating the major genotypes, despite some mistyping in the annotation of subtypes (34,35). Sequencing other viral regions is indicated for more accurate subtyping and molecular epidemiological studies (36), but this would require re-amplification of all samples after RNA detection with different pairs of primers.…”
Section: Discussionmentioning
confidence: 99%
“…Primers KY78 and KY80 were used in the reaction, as previously described, to amplify a sequence of 244 nucleotides within the conserved 5'UTR of the HCV genome. Amplified DNA was detected using target-specific oligonucleotide probes that permitted independent identification of HCV amplicons and internalcontrol amplicons [11,12].…”
Section: Detection Of Hcv Rna By the Polymerase Chain Reactionmentioning
confidence: 99%